RETRACTED: Analysis of Risk Factors Occurrence of Juvenile Delinquency Behavior - Tri Anjaswarni; Sri Widati; Ah Yusuf (Jurnal Ners, 2019)
Background: Nowadays juvenile delinquency is increasing in terms of number and type. Delinquency and criminality among teenagers are generally categorized as deviant behavior in society and can be interpreted as a form of teenage resistance to normative rules and values that apply in society. Many risk factors are related to deviant behavior. This study aimed to analyze the risk factors that influence the occurrence of juvenile delinquency.Method: This study used a cross-sectional design and a simple random sampling technique. The calculation results involved 295 samples. The independent variables were individuals, families, school environments, peer groups, coping mechanisms, lifestyles, and technologies. The dependent variable was juvenile delinquency. The data was collected using a questionnaire. The analysis used a multiple linear regression test with a significance level of α≤0.05.Results: Of the seven variables, six of them significantly influence juvenile delinquency. Technology is the variable that has the greatest influence on the occurrence of teenager wear.Conclusion: Technology is the most influential factor. These results indicate a significant shift in the causes of juvenile delinquency from family and peer factors to technological factors. This is quite reasonable because technology is a major need and is a trend for teenagers at this time.